Isoniazid (INH) a tuberculosis drug detection using turn-off fluorescent [Ce (o-Van)3 (H2O)3] probe in real samples - Rajpal; Jana S.; Ojha R.P.; Shyam R.; Prakash R. (My University, 2025)
Isoniazid (INH) is an essential antibiotic for the treatment of tuberculosis (TB). The accurate determination of its concentration in the human body is essential and must be monitored carefully because of the risk of severe side effects from prolonged use or overdosing. In this work, we synthesized a turn-off fluorescent sensor based on the coordination complex [Ce(o-Van)3(H2O)3] by a simple precipitation method using cerium (III) nitrate hexahydrate and ortho-vanillin (o-Van) in a 1:3 stoichiometric ratio. The Ce3+ ion of the complex is coordinated by three bidentate o-Van ligands and three water molecules. Structural, optical and morphological characterizations were done using HRMS, FT-IR, UV–Vis spectroscopy, XPS, XRD, SEM, and TGA was used to assess thermal stability. The sensor has been proposed to work from the mechanism where the > C=O group of the amide functionality of INH replaces a coordinated water molecule in the complex, leading to fluorescence quenching. With an optimized condition, the fluorescence emission spectra showed the linear response within the concentration ranges 14.47 μM − 147.966 μM with an excellent correlation coefficient value of R2 = 0.994. Thus, the proposed sensor had a lower limit of detection (LOD) of 1.63 μM for the INH drug. the as-synthesized [Ce(o-Van)3(H2O)3] probe provides excellent results for the selective detection of INH in pharmaceutical tablets, human urine, and blood samples of healthy people. © 2025